Effect of Neem Products and Synthetic Insecticides against Sucking Insect Pests of Cauliflower under Field Conditions - S. Shahzad Ali; Junaid Ahmed Jatoi; Syed Sohail Ahmed; Huma Rizwana; Abdual Gaffar Khoso; Fazal-ur-Rahman Bhatti; Mohammad Ibrahim Mengal; Azizullah Bugti; Shahid Ali Shahwani; Manzoor Ahmed Rind (Journal of Basic & Applied Sciences, 2017)
:A field study was carried out during 2015 at Muhammad Bachal farm at Bakrani District Larkana. Four treatments with three replications were applied. The treatments were: T1=Chemical control (Diamond 20SP), T2=Neem oil, T3= Neem kernel, T4= Untreated (Control). Two insect pests were found infesting Cauliflower including white fliesand thrips. Pre-treatment- and post-treatment observations were recorded. The results revealed that against thrips, the first spray of chemical control (Diamond) showed highest reduction percent (50.61%) followed by neem oil (43.33%), neem kernel (40.42%), and lowest for untreated control (10.31%); while in the second spray also, chemical control (Diamond) showed highest effect against thrips (58.51%); followed by neem oil (57.88%), neem kernel (52.43%) and least by untreated plot (14.77%). Against white flies chemical control (Diamond) showed highest effect (82.89%) as observed during 1st spray, followed by neem oil (72.47%), neem kernel (72.68%), and untreated control (5.12%), while after second spray also chemical control (Diamond) showed highest reduction percent (85.53%) followed by neem oil (74.34%), neem kernel (72.26%), and the lowest was resulted by untreated control (4.11%). Chemical control (Diamond) showed its superiority in effect to combat sucking insect pests studied in cauliflower, followed by neem oil, neem kernel, and untreated control remained the least.